A nano-rare earth oxide ceramic-titanium micro-alloy composite reinforced tungsten powder, composite material and preparation method thereof

CN121156253BActive Publication Date: 2026-10-30CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511372381.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2026-10-30
Estimated Expiration
2045-09-24

AI Technical Summary

Technical Problem

[0005]本发明提供了一种纳米稀土氧化物陶瓷-Ti微合金复合增强W粉末、复合材料及其制备方法,其目的是为了解决现有的W材料晶体韧性差的问题

Benefits of technology

[0037](1)本发明提供的纳米稀土氧化物陶瓷-Ti微合金复合增强W粉末尺寸约30-50nm,形成难熔金属W/Ti包覆纳米氧化物陶瓷的核壳多层级复合结构:3-5 nm尺度的氧化物陶瓷相作为内核,而Ti元素在外围形成一层15-20nm的连续壳层,烧结过程核壳多层结构原位形成纳米氧化物陶瓷全部W晶内分布,阻碍位错运动;Ti微合金元素主要以(W、Ti)ss固溶体和/或Ti单质和/或Ti的氧化物形式,在W/稀土氧化物陶瓷界面形成富集区,有效改善了界面结构和阻碍W晶界迁移,显著细化W颗粒;同时,缓释界面应力集中,部分与W基体相形成半共格,实现界面强韧化;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121156253B_ABST
    Figure CN121156253B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of nuclear fusion facing plasma W material, and particularly relates to a kind of nano rare earth oxide ceramic-Ti micro alloy composite reinforced W powder, composite material and preparation method thereof.The composite powder is near-spherical core-shell hierarchical structure, and the particle size is 30-50nm;The composite powder is with refractory metal W as matrix, and nano rare earth oxide ceramic particles are uniformly dispersed in the matrix W grain, and Ti is mainly in the form of elemental or oxide on the surface of matrix or at the interface of matrix / rare earth oxide to form enrichment zone, which effectively improves the interface structure, hinders W grain boundary migration and dislocation movement, significantly refines W grain, and partially forms semi-coherent with W, realizes fine grain and interface strengthening, and provides a new idea and technical method for synergistically improving the strength and toughness of W composite material.The composite powder is prepared into composite material by organic reduction synthesis and low-temperature strengthening sintering, and the tensile strength at room temperature reaches 500-610 MPa, and the elongation is 5%-8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nuclear fusion-oriented plasma W material technology, and particularly to a nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, composite material and its preparation method. Background Technology

[0002] Tungsten and its alloys, due to their advantages such as high melting point, high thermal conductivity, low expansion, and low sputtering threshold, are widely used in cutting-edge technologies in aerospace, nuclear energy, and defense. In particular, in recent years, tungsten materials have been used as plasma materials (PFMs) for fusion reactors in the International Thermonuclear Experimental Reactor (ITER). However, existing tungsten materials still have some shortcomings, such as low-temperature embrittlement, a high ductile-brittle transition temperature (DBTT), and a low recrystallization temperature (RCT), which greatly limit the application of tungsten materials. Oxide ceramics, due to their high melting point and chemical stability, can effectively refine tungsten grains, reduce DBTT, and improve mechanical properties as a reinforcing phase, becoming an important development direction for high-performance tungsten-PFMs.

[0003] As a composite material of W (tungsten oxide), the metal with the highest melting point, and high-melting-point oxide ceramics, conventional melting and casting methods are difficult to prepare, making powder metallurgy the preferred approach. The characteristics of the powder have a crucial impact on the performance of the composite material. Currently, the preparation of oxide-reinforced tungsten (ODS-W) composite powders typically involves mechanical alloying and wet chemical methods. Mechanical alloying can produce nanoparticles in batches and is a simple process, but it easily introduces impurities such as Ni / Fe, and the reinforcing phase nano-oxide ceramics are difficult to disperse and prone to agglomeration. Wet chemical methods can effectively control morphology and size, producing high-purity, highly uniform composite powders; however, the powder size distribution is dispersed and bimodal, leading to a decrease in sintering density and failing to significantly improve the performance of ODS-W materials. To address this, the authorized patent CN114480903 B, "A High-He Plasma Irradiation Resistant Ultrafine-Grained W-Y2O3 Composite Material and its Preparation Method," employs a nano-in-situ synthesis-sol-gel drying reduction method for W-Y2O3 composite powder. This method achieves in-situ synthesis and uniform dispersion of nano-rare earth oxides, effectively overcoming the shortcomings of mechanical alloying where nano-added phases easily agglomerate and introduce impurities. It provides excellent powder raw materials for subsequent high-He irradiation resistant W composite materials. In the composite powder prepared by this method, nano-Y2O3 is embedded on the surface of W particles, and during sintering, most of it is distributed in-situ at the W grain boundaries, pinning the grain boundaries and refining the grains, significantly improving the room temperature / high temperature strength of the W composite material. However, the nano-oxides distributed at the grain boundaries can reduce the W grain boundary strength, easily forming crack initiation and propagation channels under external loads, thus leading to reduced toughness. More importantly, fusion reactors will face extremely harsh thermal service environments for plasma materials (PFMs), including high temperatures and high steady-state / transient thermal load impacts, placing higher demands on the strength and toughness of W materials.

[0004] Therefore, there is an urgent need to develop an oxide-reinforced W composite material with synergistic improvement in strength and toughness, starting from the composite powder to improve the grain mosaic morphology and further form a composite material with high strength, toughness and high temperature resistance. Summary of the Invention

[0005] This invention provides a nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, a composite material, and a method for preparing the same, with the aim of solving the problem of poor crystal toughness in existing W materials.

[0006] To achieve the above objectives, the present invention provides a nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder. The composite powder has a near-spherical core-shell multi-level structure, with W metal as the matrix. The nano-rare earth oxide ceramic particles are uniformly dispersed within the W metal grains of the matrix, and the microalloying element Ti is distributed on the outer side of the matrix interface to form a shell, thus constituting a core-shell multi-level structure.

[0007] The composite powder has a particle size of 30-50 nm, the nano-rare earth oxide ceramic particles have a particle size of 3-5 nm, and the shell thickness is 15-20 nm.

[0008] Preferably, the nano-rare earth oxide ceramic is Y2O3 and / or La2O3, the nano-oxide ceramic particles account for 0.3~0.9% of the total mass of the composite powder, and the microalloying element Ti accounts for 0.1~1% of the total mass of the composite powder.

[0009] In the shell, the microalloying element Ti exists in the form of elemental Ti.

[0010] In composite powders, Ti microalloying elements mainly exist in the form of (W,Ti)ss solid solution and / or elemental Ti. Since W and Ti are miscible, W and Ti will first form (W,Ti)ss solid solution during the reaction process, and then some Ti will precipitate out in elemental form.

[0011] Under the same technical concept, the present invention also provides a nano-rare earth oxide ceramic-Ti microalloy composite reinforced W material, wherein the grain size of the composite material is 700~1000 nm; the composite material has W metal as the matrix, the core is nano-rare earth oxide reinforced phase grains with a grain size of 60~120 nm; the outer layer of the nano-rare earth oxide reinforced phase grains is coated with a TiO2 buffer interface with a thickness of 5~8 nm; the Ti microalloying element exists in the form of (W,Ti)ss solid solution and / or TiO2.

[0012] The composite material of this application is obtained by low-temperature strengthening sintering of nano-rare earth oxide ceramic-Ti microalloy composite reinforced W powder. During the high-temperature sintering process, the rare earth oxides, which serve as the core, are distributed in situ within the W crystals. The Ti, which serves as the shell, and some of the Ti in the (W,Ti)ss solid solution absorb oxygen to form Ti oxides, which are enriched at the W / oxide ceramic interface, improving the interface and forming a semi-coherent interface strengthening.

[0013] Preferably, the composite material has a room temperature tensile strength of 500~610 MPa and an elongation of 5%~8%.

[0014] Under the same technical concept, the present invention also provides a method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, comprising the following steps:

[0015] S1. Dissolve the W source in an organic intermediate solvent, and add dropwise a diphenyl ether solution containing titanium isopropoxide and rare earth metal isopropoxide.

[0016] S2. Using the organic reduction synthesis method, the pH of the reaction solution system is adjusted to 5-9, and the temperature is increased to the reaction temperature of 180-230℃ at a heating rate of 10-15℃ / min.

[0017] S3. During the heating process, gradually add a diphenyl ether solution containing an acid-base buffer pair;

[0018] S4. Maintain the reaction temperature under reflux until the reaction is complete, then cool to room temperature.

[0019] S5. Pour the reaction solution into anhydrous ethanol, and a black precipitate will form.

[0020] S6. The black precipitate was washed and centrifuged to obtain nano-rare earth oxide ceramic-Ti microalloyed composite powder.

[0021] By controlling the key process parameters of pH and temperature in the organic phase, a core-shell multi-level composite structure can be achieved, in which all nano-rare earth oxides are distributed within the W crystal and Ti is distributed on the W surface, with nano-rare earth oxides / W / Ti dispersedly distributed.

[0022] Specifically, the organic reduction synthesis method used in this invention prepares nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder. The pH is used to adjust the temperature of each reaction in the reaction system. As the temperature increases, the precipitation sequence of different substances can be mainly divided into the following stages:

[0023] 1. Heating to 150-180℃: Carbonyl tungsten reacts with titanium isopropoxide, and carbonyl tungsten reacts with rare earth metal isopropoxide to generate pentacarbonyl (μ-isopropoxy) (triisopropoxy titanium) tungsten and pentacarbonyl (μ-isopropoxy) (diisopropoxy yttrium) tungsten, respectively;

[0024] 2. Heating to 180-200℃: Pentacarbonyl (μ-isopropoxy) (triisopropoxytitanium) tungsten and pentacarbonyl (μ-isopropoxy) (diisopropoxyyttrium) tungsten undergo alcoholysis reactions with alcohols in organic solvents to generate Ti(OH)4 and Y(OH)3, respectively; at the same time, water is lost at this temperature to form Y2O3 and TiO2 precipitates.

[0025] 3. 180-200℃: Carbonyl tungsten decomposes into elemental W above 180℃. Therefore, elemental W adheres to the preferentially precipitated Y₂O₃ or TiO₂ nucleation sites, forming oxides as the core, with W encased in a core-shell structure. Simultaneously, pentacarbonyl (μ-isopropoxy) (triisopropoxytitanium) tungsten also undergoes a β-H elimination reaction to generate TiH₂.

[0026] 4. Above 200℃: TiO2 + TiH2 reduction reaction generates Ti, so the reaction temperature can be quickly raised to above 200℃, so that titanium oxide can quickly participate in the reduction reaction after it is formed. Since the target of the reduction reaction is on the nano tungsten clusters, a continuous titanium shell can be formed around the tungsten.

[0027] Therefore, the reaction method of the present invention can achieve preferential precipitation of nano-rare earth oxides, generation of elemental W and subsequent precipitation based on nucleation of nano-rare earth oxides, and finally precipitation of Ti. This results in W being generated on the surface of the preferentially precipitated nano-rare earth oxides, forming a W-coated nano-rare earth oxide layer, ensuring that all nano-rare earth oxides are distributed within the W crystals. Through dislocation pinning and dispersion strengthening, the strength is improved, and grain boundary segregation is avoided.

[0028] Preferably, the W source in S1 is carbonyl tungsten, and the organic intermediate solvent includes one or more of 1,2-hexadecanediol, oleylamine, or 1-octadecene.

[0029] By controlling the content of titanium isopropoxide, the occurrence of β-H elimination reaction can be increased. According to the different chemical reactions at different reaction temperature stages, at 150℃-180℃, carbonyl tungsten reacts with titanium isopropoxide to generate pentacarbonyltriisopropoxy titanium tungsten; at 180-200℃, pentacarbonyltriisopropoxy titanium tungsten will undergo two reactions: an alcoholysis reaction with organic alcohol to generate Ti(OH)4, and a separate β-H elimination reaction to generate TiH2; the content of titanium isopropoxide has a greater impact on the β-H elimination reaction. Therefore, controlling the content of titanium isopropoxide can increase the β-H elimination reaction, and the formed TiH2 will reduce TiO2 to generate elemental Ti.

[0030] Therefore, by controlling the content of titanium isopropoxide, Ti can be further precipitated as elemental titanium rather than TiO2, and Ti is reduced at reduction sites on the W surface, ultimately forming in situ on the W surface. Furthermore, Ti can be directly precipitated from the organic phase with very uniform dispersion.

[0031] The pH adjustment in the reaction solution system described in S2 is achieved using an organic acid or an organic base. The organic acid includes one or more of benzenesulfonic acid, triethyl phosphate, or trifluoroacetic acid; the organic base includes one or more of tetramethylammonium hydroxide and triethylamine.

[0032] The organic reduction reaction in step S2 is protected under an Ar2 atmosphere;

[0033] Preferably, the acid-base buffer pair in S3 is one or more of oleic acid or oleylamine; the reflux reaction time in S4 is 9h~12h; and the washing in S6 involves multiple rinsings with ethanol.

[0034] Under the same technical concept, the present invention also provides a method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite material, comprising the following steps: taking nano-rare earth oxide ceramic-Ti microalloyed composite powder, or nano-rare earth oxide ceramic-Ti microalloyed composite powder prepared by the preparation method, and molding or cold isostatic pressing, and then sintering at low temperature under a hydrogen atmosphere to obtain nano-rare earth oxide ceramic-Ti microalloyed composite material.

[0035] Preferably, the temperature of the low-temperature activation sintering is 1800-1900℃, and the holding time is 1-3h.

[0036] The above-described solution of the present invention has the following beneficial effects:

[0037] (1) The nano-rare earth oxide ceramic-Ti microalloy composite reinforced W powder provided by the present invention has a size of about 30-50 nm, forming a core-shell multi-level composite structure of refractory metal W / Ti coated nano-oxide ceramic: the oxide ceramic phase with a scale of 3-5 nm serves as the core, while the Ti element forms a continuous shell layer of 15-20 nm on the periphery. During the sintering process, the core-shell multi-level structure is formed in situ, and all W is distributed within the nano-oxide ceramic, which hinders dislocation movement. The Ti microalloying element mainly forms an enrichment zone at the W / rare earth oxide ceramic interface in the form of (W, Ti)ss solid solution and / or Ti element and / or Ti oxide, which effectively improves the interface structure and hinders W grain boundary migration, and significantly refines W particles. At the same time, it slows down the stress concentration at the interface and partially forms a semi-coherent structure with the W matrix phase, thereby achieving interface toughening.

[0038] (2) The composite material obtained by sintering the composite powder of the present invention has a grain size of 700-1000 nm, a room temperature tensile strength of 500-610 MPa, and an elongation of 5%-8%, which significantly improves the strength and toughness.

[0039] (3) This invention employs an organic reduction synthesis method, which regulates the dominant mechanism in the organic reduction process by adjusting pH, reaction temperature, and titanium isopropoxide content, so that W / rare earth / Ti elements in the organic phase are uniformly dispersed. This enables the preparation of core-shell multi-level composite powders with high uniform dispersion and high purity (W / Ti) coated rare earth oxide ceramics. Compared with wet chemical methods and sol-drying reduction methods, the reactions in the organic reduction method are all carried out at low temperature and in the organic phase, without the need for a hydrogen environment and high temperature, and have the advantages of low energy consumption, high safety, and high purity and quality. Compared with the traditional mechanical alloying method, it effectively solves the problems of easy agglomeration of nano-added phases and the introduction of impurities. Attached Figure Description

[0040] Figure 1 TEM image of W-0.3%Y2O3-0.5%Ti nanopowder prepared for an embodiment of the present invention;

[0041] Figure 2 TEM image of the microstructure of the oxide ceramic-Ti microalloyed composite reinforced nanocrystalline W-based composite material prepared in an embodiment of the present invention. Detailed Implementation

[0042] To make the technical problems, solutions, and advantages of this invention clearer, a detailed description will be provided below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0043] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0044] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a locking connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0045] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0046] Example 1:

[0047] Taking the nanocrystalline W-0.3%Y2O3-0.1%Ti composite material (100g) as an example, the composition of each element by mass percentage is as follows: Y2O3 is 0.3%, Ti is 0.1%, and the remainder is refractory metal W.

[0048] This embodiment provides a method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, the specific steps of which are as follows:

[0049] S1: Based on the above ratio, weigh 100g, 0.4g and 0.3g of carbonyl tungsten, yttrium isopropoxide and titanium isopropoxide respectively. Dissolve carbonyl tungsten in the organic intermediate solvent 1,2-hexadecanediol, and then add a diphenyl ether solution containing titanium isopropoxide and yttrium isopropoxide dropwise.

[0050] S2: Adjust the pH to 5 by adding the organic acid trifluoroacetic acid, then rapidly heat to the reaction temperature of 230℃ at a rate of 10~15℃ / min, and protect with an Ar2 atmosphere;

[0051] S3: During the heating process, a diphenyl ether solution containing 1 ml of oleic acid and oleylamine as an acid-base buffer pair is gradually added dropwise to carry out an organic reduction reaction;

[0052] S4: After the heating is completed, maintain the temperature at 230℃ under reflux for 12 h, and then gradually cool down to room temperature;

[0053] S5: Pour the cooled reaction solution into anhydrous ethanol, and a black precipitate will quickly form.

[0054] S6: The black precipitate was washed three times with ethanol and centrifuged to obtain nano-rare earth oxide ceramic-Ti microalloyed composite powder with an average size of about 46 nm. The composite powder has a near-spherical core-shell structure with W metal as the matrix. Y2O3 particles are uniformly dispersed inside the W metal grains of the matrix, and the microalloying element Ti is distributed on the outer side of the matrix interface to form a shell, constituting a core-shell multilayer structure. The particle size of Y2O3 particles is 3~5 nm, and the shell thickness is 15~20 nm.

[0055] S7: The above powder is formed by compression molding or cold isostatic pressing and sintered at 1880℃ for 2 hours in a hydrogen atmosphere to become a W-0.3%Y2O3-0.1%Ti composite material with a relative density of 96.3%. The composite material has W metal as the matrix, tungsten grain size of 987nm, Y2O3 reinforced phase grains with grain size of 100~120nm, and TiO2 buffer interface coated on the outer layer of rare earth oxide reinforced phase grains with an interface thickness of 5-8nm. Ti microalloying elements exist in the form of (W, Ti)ss solid solution and / or TiO2.

[0056] The composite material has a room temperature tensile strength of 512 MPa and an elongation of 5.1%.

[0057] Example 2:

[0058] Taking the nanocrystalline W-0.3%Y2O3-0.3%Ti composite material (100g) as an example, the composition of each element by mass percentage is as follows: Y2O3 is 0.3%, Ti is 0.3%, and the remainder is refractory metal W.

[0059] This embodiment provides a method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, the specific steps of which are as follows:

[0060] S1: Based on the above ratio, weigh 100g, 0.4g and 1g of carbonyl tungsten, yttrium isopropoxide and titanium isopropoxide respectively. Dissolve carbonyl tungsten in the organic intermediate solvent 1,2-hexadecanediol, and then add a diphenyl ether solution containing titanium isopropoxide and yttrium isopropoxide dropwise.

[0061] S2: Adjust the pH to 5 by adding the organic acid trifluoroacetic acid, then rapidly heat to the reaction temperature of 210℃ at a rate of 10~15℃ / min, and protect with an Ar2 atmosphere;

[0062] S3: During the heating process, a diphenyl ether solution containing 1 ml of oleic acid and oleylamine as an acid-base buffer pair is gradually added dropwise to carry out an organic reduction reaction;

[0063] S4: After the heating is completed, maintain the temperature at 210℃ under reflux for 12 h, and then gradually cool down to room temperature;

[0064] S5: Pour the cooled reaction solution into anhydrous ethanol, and a black precipitate will quickly form.

[0065] S6: The black precipitate was washed three times with ethanol and centrifuged to obtain nano-rare earth oxide ceramic-Ti microalloyed composite powder with an average size of about 42 nm. The composite powder has a near-spherical core-shell structure with W metal as the matrix. Y2O3 particles are uniformly dispersed inside the W metal grains of the matrix, and the microalloying element Ti is distributed on the outer side of the matrix interface to form a shell, constituting a core-shell multilayer structure. The particle size of Y2O3 particles is 3~5 nm, and the shell thickness is 15~20 nm.

[0066] S7: The above powder is formed by compression molding or cold isostatic pressing and sintered at 1860℃ for 2 hours in a hydrogen atmosphere to become a W-0.3%Y2O3-0.3%Ti composite material with a relative density of 97.5%. The composite material has W metal as the matrix, tungsten grain size of 871nm, Y2O3 reinforced phase grains with grain size of 100~120nm, and TiO2 buffer interface coated on the outer layer of the rare earth oxide reinforced phase grains with an interface thickness of 5~8nm. Ti microalloying elements exist in the form of (W, Ti)ss and / or TiO2.

[0067] The composite material has a room temperature tensile strength of 553 MPa and an elongation of 5.7%.

[0068] Example 3:

[0069] Taking the nanocrystalline W-0.3%Y2O3-0.5%Ti composite material (100g) as an example, the composition of each element by mass percentage is as follows: Y2O3 is 0.3%, Ti is 0.5%, and the remainder is refractory metal W.

[0070] This embodiment provides a method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, the specific steps of which are as follows:

[0071] S1: Weigh 100g, 0.4g and 1.66g of carbonyl tungsten, yttrium isopropoxide and titanium isopropoxide respectively according to the above proportions. Dissolve carbonyl tungsten in the organic intermediate solvent 1,2-hexadecanediol, and then add a diphenyl ether solution containing titanium isopropoxide and yttrium isopropoxide dropwise.

[0072] S2: Adjust the pH to 6 by adding the organic acid trifluoroacetic acid, then rapidly heat to the reaction temperature of 200℃ at a rate of 10~15℃ / min, and protect under an Ar2 atmosphere;

[0073] S3: During the heating process, a diphenyl ether solution containing 1 ml of oleic acid and oleylamine as an acid-base buffer pair is gradually added dropwise to carry out an organic reduction reaction;

[0074] S4: After the heating is completed, maintain the temperature at 200℃ under reflux for 9 hours, and then gradually cool down to room temperature;

[0075] S5: Pour the cooled reaction solution into anhydrous ethanol, and a black precipitate will quickly form.

[0076] S6: The black precipitate is washed three times with ethanol and centrifuged to obtain nano-rare earth oxide ceramic-Ti microalloyed composite powder with an average size of about 38 nm. The composite powder has a near-spherical core-shell structure with W metal as the matrix. Y2O3 particles are uniformly dispersed inside the W metal grains of the matrix, and the microalloying element Ti is distributed on the outer side of the matrix interface to form a shell, constituting a core-shell multilayer structure. The particle size of Y2O3 particles is 3~5 nm, and the shell thickness is 15~20 nm.

[0077] S7: The above powder is formed by compression molding or cold isostatic pressing, and sintered at 1830℃ for 2 h in a hydrogen atmosphere to form a W-0.3%Y2O3-0.5%Ti composite material with a relative density of 98.8%. The composite material has W metal as the matrix, tungsten grain size of 774nm, Y2O3 reinforced phase grains with grain size of 80~110nm, and TiO2 buffer interface with an outer layer of rare earth oxide reinforced phase grains and an interface thickness of 5~8nm. Ti microalloying elements exist in the form of (W, Ti)ss solid solution and / or TiO2.

[0078] The composite material has a room temperature tensile strength of 607 MPa and an elongation of 7.8%.

[0079] Example 4:

[0080] Taking the nanocrystalline W-0.3%Y2O3-0.9%Ti composite material (100g) as an example, the composition of each element by mass percentage is as follows: Y2O3 is 0.3%, Ti is 0.9%, and the remainder is refractory metal W.

[0081] This embodiment provides a method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, the specific steps of which are as follows:

[0082] S1: Weigh 100g, 0.4g and 3g of carbonyl tungsten, yttrium isopropoxide and titanium isopropoxide respectively according to the above proportions. Dissolve carbonyl tungsten in the organic intermediate solvent 1-octadecene, and then add a diphenyl ether solution containing titanium isopropoxide and yttrium isopropoxide dropwise.

[0083] S2: Adjust the pH to 8 by adding the organic acid trifluoroacetic acid, then rapidly heat to the reaction temperature of 180℃ at a rate of 10~15℃ / min, and protect with an Ar2 atmosphere;

[0084] S3: During the heating process, a diphenyl ether solution containing 1 ml of oleic acid and oleylamine as an acid-base buffer pair is gradually added dropwise to carry out an organic reduction reaction;

[0085] S4: After the heating is completed, maintain the temperature at 200℃ under reflux for 9 hours, and then gradually cool down to room temperature;

[0086] S5: Pour the cooled reaction solution into anhydrous ethanol, and a black precipitate will quickly form.

[0087] S6: The black precipitate is washed three times with ethanol and centrifuged to obtain nano-rare earth oxide ceramic-Ti microalloyed composite powder with an average size of about 33 nm. The composite powder has a near-spherical core-shell structure with W metal as the matrix. Y2O3 particles are uniformly dispersed inside the W metal grains of the matrix, and the microalloying element Ti is distributed on the outer side of the matrix interface to form a shell, constituting a core-shell multilayer structure. The particle size of Y2O3 particles is 3~5 nm, and the shell thickness is 15~20 nm.

[0088] S7: The above powder is formed by compression molding or cold isostatic pressing and sintered at 1800℃ for 2 h in a hydrogen atmosphere to become a W-0.3%Y2O3-0.9%Ti composite material with a relative density of 97.8%. The composite material has W metal as the matrix, tungsten grain size of 847nm, Y2O3 reinforced phase grains with grain size of 60~90nm, and TiO2 buffer interface coated on the outer layer of rare earth oxide reinforced phase grains with an interface thickness of 5~8nm. Ti microalloying elements exist in the form of W and Ti ss solid solution and / or TiO2.

[0089] The composite material has a room temperature tensile strength of 542 MPa and an elongation of 8.0%.

[0090] Example 5:

[0091] Taking the nanocrystalline W-0.3%La2O3-0.5%Ti composite material (100g) as an example, the composition of each element by mass percentage is as follows: La2O3 is 0.3%, Ti is 0.5%, and the remainder is refractory metal W.

[0092] This embodiment provides a method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, the specific steps of which are as follows:

[0093] S1: Weigh 100g, 0.35g and 1g of carbonyl tungsten, lanthanum isopropoxide and titanium isopropoxide respectively according to the above proportions. Dissolve carbonyl tungsten in the organic intermediate solvent 1,2-hexadecanediol, and then add a diphenyl ether solution containing titanium isopropoxide and lanthanum isopropoxide dropwise.

[0094] S2: Adjust the pH to 6 by adding the organic acid trifluoroacetic acid, then rapidly heat to the reaction temperature of 210℃ at a rate of 10~15℃ / min, and protect under an Ar2 atmosphere;

[0095] S3: During the heating process, a diphenyl ether solution containing 1 ml of oleic acid and oleylamine as an acid-base buffer pair is gradually added dropwise to carry out an organic reduction reaction;

[0096] S4: After the heating is completed, maintain the temperature at 210℃ under reflux for 10 h, and then gradually cool down to room temperature;

[0097] S5: Pour the cooled reaction solution into anhydrous ethanol, and a black precipitate will quickly form.

[0098] S6: The black precipitate was washed three times with ethanol and centrifuged to obtain nano-rare earth oxide ceramic-Ti microalloyed composite powder with an average size of about 46 nm. The composite powder has a near-spherical core-shell structure with W metal as the matrix. La2O3 particles are uniformly dispersed inside the W metal grains of the matrix, and the microalloying element Ti is distributed on the outer side of the matrix interface to form a shell, constituting a core-shell multilayer structure. The particle size of La2O3 particles is 3~5 nm, and the shell thickness is 15~20 nm.

[0099] S7: The above powder is formed by compression molding or cold isostatic pressing and sintered at 1830℃ for 2 h in a hydrogen atmosphere to become a W-0.3%La2O3-0.5%Ti composite material with a relative density of 98.1%. The composite material has W metal as the matrix, tungsten grain size of 817nm, core of La2O3 reinforced phase grains with grain size of 80~110nm, and outer layer of rare earth oxide reinforced phase grains coated with TiO2 buffer interface with an interface thickness of 5~8nm. Ti microalloying element exists in the form of W and Ti ss solid solution and / or TiO2.

[0100] The composite material has a room temperature tensile strength of 563 MPa and an elongation of 7.6%.

[0101] The prepared W-0.3%Y2O3-0.5%Ti nanocomposite powder was characterized as follows: Figure 1As shown, (a) is the morphology of the composite powder, (b) is the HRTEM of a selected area, and (c) and (d) are magnified views of the corresponding HRTEM in (b). It can be seen that the composite powder exhibits a distinct core-shell structure with an average particle size of about 30-50 nm and a shell thickness of about 15-20 nm. Among them, Y2O3 (d=0.2651 nm, (400)) is distributed as a 3-5 nm small core inside the W grains; while Ti exists in the form of (W,Ti)ss solid solution and Ti element (d=0.2341 nm, (002)), distributed around the tungsten grains, forming a continuous shell.

[0102] TEM images of the nanocrystalline W-0.3%Y2O3-0.5%Ti composite material after sintering at 1800℃ are shown below. Figure 2 (a) Bright field image; (b) HRTEM corresponding to the selected region; (ce) Enlarged view of the region corresponding to the HRTEM; (fh) Interplanar spacing test of the corresponding HRTEM. It shows that nano-rare earth Y2O3 (d=0.2583 nm, Y2O3(125)) is distributed in the W matrix crystal, with a grain size of 60-120 nm, which can hinder dislocation movement. The outer layer is a widely distributed W matrix phase (d=0.2288 nm, W(110)). Ti dissolves and precipitates at the rare earth Y2O3 / W interface to form an enriched region, and absorbs oxygen to generate TiO2 (d=0.2361 nm, TiO2(121)), which serves as a buffer interface with a thickness of 5-8 nm. Meanwhile, the mismatch degree of W (110) and TiO2 (121) at the interface is 3.09%, and the mismatch degree of TiO2 (121) and Y2O3 (125) is 8.59%, both forming a semi-coherent structure, effectively achieving interface toughening.

[0103] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W powder, characterized in that, Includes the following steps: S1. Dissolve the W source in an organic intermediate solvent, and add dropwise a diphenyl ether solution containing titanium isopropoxide and rare earth metal isopropoxide. S2. Using the organic reduction synthesis method, the pH of the reaction solution system is adjusted to 5~9, and the temperature is increased to the reaction temperature of 180℃~230℃ at a heating rate of 10~15℃ / min. S3. During the heating process, gradually add a diphenyl ether solution containing an acid-base buffer pair; S4. Maintain the reaction temperature under reflux until the reaction is complete, then cool to room temperature. S5. Pour the reaction solution into anhydrous ethanol, and a black precipitate will form. S6. Wash the black precipitate and centrifuge to obtain nano-rare earth oxide ceramic-Ti microalloyed composite powder. The composite powder has a near-spherical core-shell multi-level structure. With W metal as the matrix, nano-rare earth oxide ceramic particles are uniformly dispersed inside the W metal grains of the matrix, and micro-alloying element Ti is distributed on the outside of the matrix to form a shell, thus constituting a core-shell multi-level structure. The composite powder has a particle size of 30-50 nm, the nano-rare earth oxide ceramic particles have a particle size of 3-5 nm, and the shell thickness is 15-20 nm.

2. The preparation method according to claim 1, characterized in that, The nano-rare earth oxide ceramic particles are Y2O3 and / or La2O3, and the nano-rare earth oxide ceramic particles account for 0.3-0.9% of the total mass of the composite powder, while the microalloying element Ti accounts for 0.1-1% of the total mass of the composite powder. In the shell, the microalloying element Ti exists in the form of elemental Ti.

3. The preparation method according to claim 1, characterized in that, The W source mentioned in S1 is carbonyl tungsten, and the organic intermediate solvent includes one or more of 1,2-hexadecanediol, oleylamine, or 1-octadecene.

4. The preparation method according to claim 1, characterized in that, The pH adjustment in the reaction solution system described in S2 is achieved using an organic acid or an organic base. The organic acid includes one or more of benzenesulfonic acid, triethyl phosphate, or trifluoroacetic acid; the organic base includes one or more of tetramethylammonium hydroxide and triethylamine. The organic reduction synthesis reaction in step S2 is protected under an Ar atmosphere.

5. The preparation method according to claim 1, characterized in that, The acid-base buffer pair mentioned in S3 is one or more of oleic acid or oleylamine; the reflux time mentioned in S4 is 9h to 12h; the washing mentioned in S6 uses ethanol for multiple rinsing.

6. A method for preparing a nano-rare earth oxide ceramic-Ti microalloyed composite reinforced W material, characterized in that, Includes the following steps: The nano-rare earth oxide ceramic-Ti microalloyed composite powder prepared by the preparation method according to any one of claims 1-5 is subjected to molding or cold isostatic pressing and then activated and sintered at low temperature in a hydrogen atmosphere to obtain the nano-rare earth oxide ceramic-Ti microalloyed composite material.

7. The preparation method according to claim 6, characterized in that, The temperature for the low-temperature activation sintering is 1800–1900℃, and the holding time is 1–3 hours.

8. The preparation method according to claim 6, characterized in that, The composite material has a grain size of 700–1000 nm. The composite material uses W metal as the matrix and the core is nano-rare earth oxide reinforced phase grains with a grain size of 60–120 nm. The outer layer of the nano-rare earth oxide reinforced phase grains is coated with a TiO2 buffer interface with a thickness of 5–8 nm. The Ti microalloying element exists in the form of (W, Ti)ss solid solution and / or TiO2.

9. The preparation method according to claim 6, characterized in that, The composite material has a room temperature tensile strength of 500–610 MPa and an elongation of 5%–8%.

Citation Information

Patent Citations

  • Preparation method of high-density fine-grain tungsten-based material

    CN109457159A

  • Method for fabricating core-shell particles and core-shell particles fabricated by the method

    US20150037711A1